"...they should be offering it": a qualitative study to investigate young peoples' attitudes towards chlamydia screening in GP surgeries - Wallace Louise M; Pottinger Elizabeth; Howell-Jones Rebecca S; Hogan Angela H; McNulty Cliodna AM (BMC, 2010)
Abstract Background Despite the known health and healthcare costs of untreated chlamydia infection and the efforts of the National Chlamydia Screening Programme (NCSP) to control chlamydia through early detection and treatment of asymptomatic infection, the rates of screening are well below the 2010-2011 target rate of 35%. General Practitioner (GP) surgeries are a key venue within the NCSP however; previous studies indicate that GP surgery staff are concerned that they may offend their patients by offering a screen. This study aimed to identify the attitudes to, and preferences for, chlamydia screening in 15-24 year old men and women attending GP surgeries (the target group). Methods We undertook 36 interviews in six surgeries of differing screening rates. Our participants were 15-24 year olds attending a consultation with a staff member. Data were analysed thematically. Results GP surgeries are acceptable to young people as a venue for opportunistic chlamydia screening and furthermore they think it is the duty of GP surgery staff to offer it. They felt strongly that it is important for surgery staff to have a non-judgemental attitude and they did not want to be singled out as 'needing' a chlamydia screen. Furthermore, our sample reported a strong preference for being offered a screen by staff and providing the sample immediately at the surgery rather than taking home a testing kit. The positive attitude and subjective norms demonstrated by interviewees suggest that young peoples' behaviour would be to accept a screen if it was offered to them. Conclusion Young people attending GP surgeries have a positive attitude towards chlamydia screening and given the right environment are likely to take up the offer in this setting. The right environment involves normalising screening by offering a chlamydia screen to all 15-24 year olds at every interaction with staff, offering screening with a non-judgemental attitude and minimising barriers to screening such as embarrassment. The GP surgery is the ideal place to screen young people for chlamydia as it is not a threatening place for them and our study has shown that they think it is the normal place to go to discuss health matters.